HUMAN RESOURCES DEVELOPMENT STRATEGY ON QUALITY IMPROVEMENT OF POSTGRADUATE LECTURERS AT IAIN CURUP - Jumira Warlizasusi; Ifnaldi Ifnaldi; Lendrawaty Lendrawaty; Hartini Hartini; Fathur Rizki (Ta'dib, 2021)
The purposes of this research are to find out a) the strategies in human resources development to improve the quality of Postgraduate lecturers at IAIN Curup, (b) supporting factors, and  (c) the obstacles of human rights development. Using qualitative research method, the data were collected through interviews and documentary study. The research results showed that the strategies used for developing human resources or improving the quality of postgraduate lecturers include: (1) organizing the research methodology training; (2) holding the scientific journal writing training; (3) holding book writing/teaching materials training; and (4) involving lecturers into National and International Seminars. Supporting factors for human resource development are (a) high commitmentof  IAIN Curup Postgraduate management, (b) organization and socialization activities for professors acceleration programs, and (c) conducting coaching clinic activities for reputable international publications, in the form of programs to publish research results in reputable international scientific journals. Meanwhile, the obstacles are inadequate infrastructure and limited funds because there are still few students and tuition fee is still in the third category in the Ministry of Religion's General Cost Standards (SBU). The funds have not been fully handed over to the Postgraduate, because it is still centralized at the Institute, if the Postgraduate organize an activity, it must be approved by the Institute before it run.